The Influence of E-trust and E-Servqual on E-Repurchase Intention with E-Satisfaction as an Intervening Variable - Apidana, Yordan; Prasetyo, Anton (Jurnal Ilmiah Manajemen Kesatuan, 2023)
The significance of e-commerce in the digital economy relies on repeat customers for sustainable growth. Key factors influencing customer return visits include e-trust and e-service quality. E-trust involves trust in platform security, product reliability, and transaction transparency. E-service quality includes website quality, responsive customer service, and efficient shipping and returns processes. This research aims to analyze the influence of E-trust and E-Servqual on E-Repurchase Intention with E-Satisfaction as an intervening variable. The study adopts a quantitative research approach, with the sample selected using nonprobability sampling, specifically the purposive sampling technique. The sample for this study comprises 244 students from Putra Bangsa University. Data analysis employs the Structural Equation Model (SEM) approach. Based on the data analysis, the following findings emerge: (1) E-trust has a positive effect on E-satisfaction, (2) E-service quality has a positive effect on E-satisfaction, (3) E-satisfaction has a positive effect on E-revisit intention, (4) E-satisfaction mediates the influence between E-trust and E-revisit intention, and (5) E-satisfaction mediates the influence between E-service quality and E-revisit intention.The results of this research have significant implications for businesses using e-commerce platforms, indicating that building trust, improving service quality, and increasing customer satisfaction are important strategies for influencing repurchase intentions in the online environment.